1980
DOI: 10.3382/ps.0590976
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Chickens with a Clone-Selected Lastoa Strain of Newcastle Disease Virus ,

Abstract: A cone-selected Lasota strain of Newcastle disease (ND) was found to be more immunogenic than the B1 strain but less immunogenic than the regular Lasota strain while having the same pathogenic index as the B1 strain. The geometric mean hemagglutination-inhibition (HI) titers induced in chickens vaccinated with the cloned Lasota strain were higher than those induced in chickens vaccinated with the B1 strain but were found to be slightly less than the titers obtained in chickens vaccinated with the regular Lasot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Results of this work could be referred to the difference in the potency and in the immunogenicity or the antigenic relation between the vaccinal and the challenge strain. Similar explanation was stated (Schloer et al, 1975;Eidson and Kleven, 1980;Russel and Alexander, 1983).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Results of this work could be referred to the difference in the potency and in the immunogenicity or the antigenic relation between the vaccinal and the challenge strain. Similar explanation was stated (Schloer et al, 1975;Eidson and Kleven, 1980;Russel and Alexander, 1983).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the field ND viruses are found to be different antiginically from the used vaccines (Panshsin et al, 2002). Eidson and Kleven, (1980) stated that ND vaccinal strains had the same pathogenic index differ in their immunogenicity based on geometric mean titers and challenge.…”
mentioning
confidence: 99%
“…Field and diagnostic laboratory reports together with published information have suggested that such changes, within strains, have perhaps occurred (Eidson et al, 1977;Eidson and Kleven, 1980;Zygraich et al, 1978). It has been reported to the authors that some have been cloned and others passaged through chickens in attempts to increase their immunogenicity and also reduce pathogenicity.…”
Section: Introductionmentioning
confidence: 88%
“…The ND strains show heterogenicity in size of plaques which may lead to the level of post-vaccination reactions usually associated with the use of live ND vaccines. Cloned vaccines which contain only one set of genetic information have the advantage of being more stable than mixed virus strain vaccines (11)(12)(13). This study attempts to select a homogenous population from LaSota strain of NDV and to introduce it as a candidate for developing a live vaccine against ND.…”
Section: Introductionmentioning
confidence: 99%
“…Lentogenic strains such as the Hitchner B1 and LaSota are widely used as live vaccines against ND (9). The vaccines are mixtures of sub-populations which differ significantly from each other in immunogenicity and pathogenicity (10,11). These sub-populations may differ in plaque morphology which correlates with virus virulence.…”
Section: Introductionmentioning
confidence: 99%